Skin care physicians insight on epidemiological patterns, diagnosis and treatment modalities for female pattern hair loss - Kilaru, Krishna Rajesh; Attada, Suhasini; Munnangi, Pooja; Kilaru, Manogna Chowdary (International Journal of Research in Dermatology, 2020)
Background: Female pattern hair loss (FPHL) is a common cause of hair loss in women characterized by a diffuse reduction in hair density over the crown and frontal scalp with retention of the frontal hairline. The underlying pathophysiology is multifactorial. There are no universally agreed treatment guidelines available. The objective of the study was to understand the diagnosis and treatment pattern of female pattern hair loss and the role of minoxidil topical formulation and its combination in the management of FPHL. Methods: Predesigned questionnaire on FPHL was prepared based on review of literature and was filled by 80 consultant dermatologists. Recorded data was statistically analyzed. Results: Common age of onset of FPHL was between 20 to 30 years. Majority (96.25%) have reported FPHL in association with psychological morbidity. The most preferred treatment in mild and severe FPHL was minoxidil 5% and platelet rich plasma (PRP) plus minoxidil respectively. Most dermatologists (47.5%) treated with minoxidil for over 6 months. Majority (27.5%) reported flaking as the most common side effect with minoxidil followed by dryness, scalp irritation and itching. Majority (27.5%) observed that long treatment duration was contributing to non-compliance followed by medication cost and side effects. Majority of the dermatologists (90%) felt the need for treatment guidelines in the current Indian scenario. Conclusions: Minoxidil was the most common preferred treatment for mild and severe FPHL. PRP is the most common choice of combination therapy with minoxidil. Minimizing side effects, patient education and universal treatment guidelines can help manage FPHL better.